Remote Sensing for Mapping the Distribution of Poverty and Inequality in Gunungkidul Regency, Yogyakarta Special Region - Anatansyah Ayomi Anandari (Proceeding International Conference on Religion, Science and Education, 2023)
Remote sensing is a technology to make it easier to make maps and analyze an area without having direct contact with the object to be studied. This study uses a remote sensing method that can be applied to social mapping, namely in making maps of the distribution of poverty. Poverty is a very complex problem in society and is influenced by many factors, including environment, health, income level, and location of residence. Therefore, there is a need for proper poverty alleviation. The Poverty Distribution Map is one of the map prototypes, which can be used to display spatially based poverty data. Poverty data, which is usually displayed in the form of numbers or indexes, can be displayed on a map sheet or visualized, making it easier to understand the condition of poverty in the community. Mapping was carried out using satellite image data sources in Gunungkidul Regency, Yogyakarta Special Region Province, Indonesia. This study aims to interpret maps of the distribution of poverty, poverty conditions and community welfare through satellite imagery so that people's lives can be easily monitored by the government. In addition, poverty data can be updated, so that the availability of data is always up to date. Gunungkidul Regency has a Percentage of Poor Population value from 2014 to 2021 which almost always increases every year. Based on the analysis that has been carried out, a mapping is obtained, where the sub-districts included in the very poor category are the sub-districts of Semanu, Ponjong, Gedangsari, and Semin.